2016
DOI: 10.1026/0943-8149/a000166
|View full text |Cite
|
Sign up to set email alerts
|

Autonomie als Prädiktor intrinsischer Motivation im Schulsport

Abstract: Autonomy as a Predictor of lntrinsic Motivation in Physical Education Classes: A Person x Situation PerspectiveAbstract: Autonomy support is considered as an important predictor of intrinsic motivation in sport environments. Referring to previous studies, which showed that the relationship between autonomy and motivation is influenced by an autonomy disposition, we aim to test the underlying fit hypothesis of intrinsic motivation in physical education classes. lt is assumed that autonomy-supportive instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The results of the studies underline the importance of supporting student autonomy to satisfy the three BPN of autonomy, competence and relatedness [75][76][77], and for improving the more self-determined motivation [78][79][80], thus supporting the results of the present study. Autonomous motivation takes place when students perceive that they are in an environment that supports autonomy [81][82][83][84], as many studies have determined the existence of a relationship between the satisfaction of BPN with more self-determined forms of motivation during PE classes [85][86][87][88][89]. This more self-determined motivation is associated with positive consequences, such as the intention to be physically active.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the studies underline the importance of supporting student autonomy to satisfy the three BPN of autonomy, competence and relatedness [75][76][77], and for improving the more self-determined motivation [78][79][80], thus supporting the results of the present study. Autonomous motivation takes place when students perceive that they are in an environment that supports autonomy [81][82][83][84], as many studies have determined the existence of a relationship between the satisfaction of BPN with more self-determined forms of motivation during PE classes [85][86][87][88][89]. This more self-determined motivation is associated with positive consequences, such as the intention to be physically active.…”
Section: Discussionmentioning
confidence: 99%
“…Sieber et al (2019) showed that autonomous goal striving promotes the endorsement of non-limited theories mediated through vitality, the experience that tasks are energizing. However, autonomous task selection and pursuit might also be challenging and overtaxing for some children (Sieber et al, 2016). The change from strong external regulation by primary caregivers in early childhood to complete internalization of regulation is a central process in the development of self-regulatory competence (Kochanska et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Undergraduate students and physically inactive people with a strong autonomy disposition benefited more strongly from the basic need for autonomy satisfaction in terms of flow experience and well‐being. Sieber, Wegner, and Schüler () extended this result pattern by testing intrinsic motivation of students in a physical education class in school. Again, supporting the matching hypothesis, students with a strong autonomy motive (assessed using DeCharms and Plimpton’s scoring system) showed significantly higher intrinsic motivation in an autonomy‐supportive group than in an autonomy‐restrictive group or in a control group, and compared to participants with a weak autonomy disposition.…”
Section: Diverging Aspects Of Mdt and Sdtmentioning
confidence: 91%
“…The results fit well into our theoretical considerations and are in accordance with a series of previous studies conducted to test the Affiliation Motive × Need for Relatedness and Achievement Motive × Need for Competence interactions. Whereas the authors’ analyses in the domains of affiliation and achievement have focused on self‐reported facets of motivation (e.g., intrinsic motivation, flow) and well‐being (e.g., affect; Schüler & Brandstätter, ; Schüler et al, ), the studies in the autonomy domain are broader and additionally include objectively assessed physiological stress responses (Schüler et al, ; Sieber, Schüler, et al, ; Sieber, Wegner, et al, ). Empirical support for physiological responses in the affiliation and achievement domains has yet to be provided, and long‐term effects of Motive × Need Satisfaction interactions on physiological responses still need to be tested.…”
Section: Diverging Aspects Of Mdt and Sdtmentioning
confidence: 99%